USE OF ANYFLIP BEKEL LONGAN E-BOOK TO IMPROVE LITERATION SKILLS OF V-GRADE STUDENTS IN KEDUNGREJO ELEMENTARY SCHOOL 2 IN PANDEMIC - Martin Indah (Widyagogik, 2021)
The purpose of this study was to determine the extent to which students' language literacy skills, especially the reading skills of students, using E-Book Anyflip with Local Wisdom in Lamongan during the pandemic. This type of research is classroom action research adopting the Kemmis and Mc. Taggart. This research uses 3 types of data (learning implementation data, student learning outcomes data, and data on constraints encountered in learning activities). The research was conducted in class V SDN 2 Kedungrejo, Modo District, Lamongan Regency. This research was conducted in two cycles, the research subjects were the fifth grade students of SDN 2 Kedungrejo in the second semester of the 2019/2020 academic year with a total of 13 students (8 male and 5 female) . The results of this study were 100% learning implementation cycle I and II. The achievement of teacher activities in learning in cycle I was 75, while in cycle II it was 87.5. The class average value of student literacy learning outcomes in the first cycle was 67.5. Meanwhile, in cycle II the average value of student literacy learning outcomes increased to 78.8. Classical learning completeness of students' literacy learning outcomes in the first cycle obtained a percentage of 69.23% and was included in the high category. Meanwhile, classical learning completeness in cycle II obtained a percentage of 92.3%. The conclusion of this study is the reading skills of students in using E-Book Anyflip with Local Wisdom in Lamongan during the pandemic are very good based on the 3 types of data used.